Analisis Miskonsepsi dalam Pembelajaran Pendidikan Jasmani SDN Karangsari - H. Soro, Suharyanto; Suherman, Maman; Astuti, Cahyanti Yuni; Mulyani, Novi Silvia; Mirawati, Mirawati (LP. Ma'arif Janggan Magetan, 2024)
hysical education has an important role in building students character. This subject I learned at primary schools. The misconceptions identified include the perception that certain sports activities are only suitable for boys or girls, which affects student participation in learning. This study aims to analyze misconceptions in Physical Education learning at SDN Karangsari, Ciranjang District, and provide solutions based on the principles of educational philosophy.. The approach used in this research is a case study with a qualitative research design. Data collection methods include observation, interviews, and documentation. Observation focused on academic activities of students, while interviews involved teachers, the principal, and students, using face-to-face interview techniques and recording. The collected data were analyzed descriptively to identify the misconceptions and provide recommendations for solutions. The results of the study indicate that these misconceptions stem from a lack of understanding of the fundamental concepts in physical education, particularly regarding gender stereotypes that associate some sports with a specific gender. Teachers tend to focus on teaching sports without explaining the underlying theories, while students have compartmentalized views on sports activities based on gender. As solutions, this study recommends teacher training, the development of an inclusive curriculum, and socialization to parents to address these misconceptions. With the implementation of these solutions, it is expected that Physical Education learning can become more inclusive and free from gender stereotypes, enabling students to fully understand and master the material.